2022
DOI: 10.1017/cjn.2022.326
|View full text |Cite
|
Sign up to set email alerts
|

Spasticity Management Teams, Evaluations, and Tools: A Canadian Cross-Sectional Survey

Abstract: Objective: The objective of this study is to determine the physical evaluations and assessment tools used by a group of Canadian healthcare professionals treating adults with spasticity. Methods: A cross-sectional web-based 19-question survey was developed to determine the types of physical evaluations, tone-related impairment measurements, and assessment tools used in the management of adults with spasticity. The survey was distributed to healthcare professionals from the Canadian Advan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…The efficacy of BoNT-A in the treatment of PS-SMD has been extensively studied. BoNT-A is considered as the treatment of choice for focal, multi-focal, and segmental PS-SMD, including spastic hypertonia, increased muscle tone, spastic dystonia, clonus, and spasms [ 2 , 3 , 5 , 6 ].…”
Section: Management Of Ps-smdmentioning
confidence: 99%
See 1 more Smart Citation
“…The efficacy of BoNT-A in the treatment of PS-SMD has been extensively studied. BoNT-A is considered as the treatment of choice for focal, multi-focal, and segmental PS-SMD, including spastic hypertonia, increased muscle tone, spastic dystonia, clonus, and spasms [ 2 , 3 , 5 , 6 ].…”
Section: Management Of Ps-smdmentioning
confidence: 99%
“…PSS or PS-SMD that is perceived by the affected individual or care giver as hindering body functions, activities, and/or participation is defined as disabling PSS or disabling PS-SMD [ 2 , 4 ]. Published prevalent data of a severe spasticity (defined as increased muscle tone equal or more than 2 of the modified Ashworth scale [MAS]) and a disabling PSS (defined as spasticity that does need treatment) showed that up to 13%–16% of stroke survivors suffer from this complication after stroke [ 2 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%